The hive bicycle hub design - Mohyin, Nur Affah; Abdul Rahim, Asiah; Alias, Nur Ulfah Awatif Umairah; Bahrudin, Fadzli Irwan; Che Haron, Roziha (IIUM Press, 2024)
The International Islamic University Malaysia (IIUM) is committed to fostering a sustainable and bike-friendly campus environment as part of its broader green initiative. This research seeks to identify a comprehensive design approach for a bicycle hub facility that resolves bicycle users' issues, such as bicycle safety and storage facilities. Utilising a qualitative approach, data was gathered through case studies, surveys, and observations. A multidisciplinary KAED student group named "Arkana", comprised of architecture, quantity surveying, and applied arts and design students, collaborated to design the bicycle hub facility. The beehive concept has been applied to establish a connection between bicycle users and nature to create a sustainable campus and develop a healthy mindset for a greener future in IIUM. The "Hive" bicycle hub design includes a modular hexagonal honeycomb structure that enhances durability, accessibility, safety, and convenience to encourage increased bicycle use among students and staff of IIUM. Key features include sheltered bicycle storage, a repair workshop, a retail outlet for bicycle parts and accessories, a cafeteria, a washroom, and a locker room. The "Hive" bicycle hub supports IIUM's sustainability goals, reduces carbon emissions, and promotes a healthier campus lifestyle by providing these amenities. Its design incorporates universal and passive principles, including natural lighting, ventilation, and a rainwater collection system. The project is expected to significantly contribute to the university's green initiatives and create a model for other institutions aiming to adopt similar bike-friendly strategies.